2014
DOI: 10.1111/1475-6773.12199
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Effects of a Breastfeeding Support Program on Health Outcomes

Abstract: Objective. To estimate the causal effect of a Michigan peer counselor (PC) breastfeeding support program for low-income women on infant health outcomes. Data Sources. Program referral forms, program forms (enrollment, birth, and exit data), and state administrative data from the Women Infants and Children program, Medicaid, and Vital Records. Study Design. Quasi-random enrollment due to the excess demand for PC breastfeeding support services allowed us to compare the infants of women who requested services and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…; Haider et al. ). These studies found the use of lactation consultants and peer or role models for counseling increased breastfeeding duration and intensity.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…; Haider et al. ). These studies found the use of lactation consultants and peer or role models for counseling increased breastfeeding duration and intensity.…”
mentioning
confidence: 98%
“…education, and about 59-60 percent of Hispanic and black mothers attempt to breastfeed their newborns, according to vital statistics records. 1 Studies have shown that the use of lactation services, including lactation consultants and breast pumps, can increase both a woman's commitment to and her success with breastfeeding (Bonuck et al 2005;Olson et al 2010;Haider et al 2014). These studies found the use of lactation consultants and peer or role models for counseling increased breastfeeding duration and intensity.…”
mentioning
confidence: 99%
“…Study paper(Gross et al, 2009); sibling qualitative study(Gross et al, 2015); training package (United States Department of Agriculture (USDA), n.d., accessed 2017)Yun et al (2010); training package (loving support and peer counselling training, accessed 2017) paper(Di Meglio et al, 2010); training package (La Leche league International, n.d., accessed 2017) paper(Olson et al, 2010); sibling study-health outcomes evaluation(Haider, Chang, Bolton, Gold, & Olson, 2014); sibling study-analysis of participant characteristics(Bolton, Chow, Benton, & Olson, 2009); training package (loving support and peer counselling training, et al (2013); training package (La Leche league International, n.d., accessed 2017)…”
mentioning
confidence: 99%
“…The course of lactation and breastfeeding is an element of multidisciplinary medical care, which should be carried out by competent, friendly personnel knowing how to communicate properly. It is common that success in breastfeeding is dependent on the new mother being surrounded by competent and friendly people to assist her with overcoming difficulties (Haider, Chang, Bolton, Gold, & Olson, 2014).…”
Section: Introductionmentioning
confidence: 99%